1999
DOI: 10.1165/ajrcmb.21.1.3517
|View full text |Cite
|
Sign up to set email alerts
|

5-Oxo-6,8,11,14-Eicosatetraenoic Acid Induces Important Eosinophil Transmigration through Basement Membrane Components

Abstract: Basement membrane transmigration is an important step in tissue recruitment of eosinophils into inflamed tissue. Recent reports showed that this phenomenon is modulated by platelet-activating factor (PAF) in combination with cytokines and proteinases. We investigated the in vitro efficacy of 5-oxo-6,8,11, 14-eicosatetraenoic acid (5-oxo-ETE), a metabolite of arachidonic acid and known as a potent eosinophil chemotactic factor, in promoting the transmigration of blood eosinophils from normal and asthmatic subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
73
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 38 publications
3
73
0
Order By: Relevance
“…The boldface letters represent amino acids conserved in all of the prostanoid receptors aligned in Fig 6. The conserved amino acids in the prostanoid receptor are also found in TG1019: 103 5-oxo-ETE exhibited the most potent agonistic activity against TG1019. This eicosanoid is known as a potent chemotactic factor of eosinophils and neutrophils (37)(38)(39)(40). O'Flaherty et al (41,42), and O'Flaherty and Rossi (43) had revealed that the chemotactic activity would be mediated through a pertussis toxin-sensitive GPCR.…”
Section: Fig 5 Effect Of 5-oxo-ete On Forskolin-stimulated Camp Promentioning
confidence: 99%
“…The boldface letters represent amino acids conserved in all of the prostanoid receptors aligned in Fig 6. The conserved amino acids in the prostanoid receptor are also found in TG1019: 103 5-oxo-ETE exhibited the most potent agonistic activity against TG1019. This eicosanoid is known as a potent chemotactic factor of eosinophils and neutrophils (37)(38)(39)(40). O'Flaherty et al (41,42), and O'Flaherty and Rossi (43) had revealed that the chemotactic activity would be mediated through a pertussis toxin-sensitive GPCR.…”
Section: Fig 5 Effect Of 5-oxo-ete On Forskolin-stimulated Camp Promentioning
confidence: 99%
“…Even more persuasive is the finding that in the IL-13 Ϫ/Ϫ mice, which also had almost no intraepithelial eosinophils, expression of eotaxin was comparable with wild-type mice and was sustained for a longer period. The additional signal or signals might include rapidly generated mediators, such as eosinophil-selective arachidonic acid metabolites (Guilbert et al, 1999), which may be particularly important in the early recruitment of eosinophils; a variety of other eosinophil chemoattractant cytokines, eg, macrophage inflammatory protein-1␣ (Campbell et al, 1998;Gonzalo et al, 1998); as well as molecules involved in the adhesion of eosinophils to vascular endothelium (Burke-Gaffney and Hellewell, 1998;Nakajima et al, 1994). In this context, IL-13 is able to up-regulate the expression of eosinophil-selective adhesion molecules such as VCAM-1 and P-selectin on endothelial cells (Bochner et al, 1995;Woltmann et al, 2000), and it is possible that absence of such upregulation accounts for the lack of eosinophil recruitment in IL-13 Ϫ/Ϫ mice.…”
Section: Figurementioning
confidence: 99%
“…In the case of eosinophils, a range of relatively selective chemoattractants for these cells has been identified, including eicosatetraenoic acid derivatives (Guilbert et al, 1999) and members of the CC chemokine family, notably eotaxin, RANTES, and various molecules of the monocyte chemoattractant protein (MCP) group (Kita and Gleich, 1996;Rothenberg et al, 1999;Teran, 2000). Potentially selective adhesion molecules that may play a critical role in eosinophil accumulation have also been described, in particular very late antigen 4 (VLA-4) and vascular cell adhesion molecule-1 (VCAM-1) (Bochner, 2000;Henricks et al, 1997).…”
mentioning
confidence: 99%
“…The contractile effects of 5-oxo-ETE on ASM were inhibited by the selective TXA 2 receptor (TP receptor) antagonist SQ-29548 (Ϫ75%) and by 2-(p-amylcinnamoyl) amino-4-chlorobenzoic acid pretreatment, a phospholipase A 2 inhibitor (Ϫ66%), suggesting that the major part of its effect is mediated by the release of TXA 2. ASM responses to 5-oxo-ETE were also blocked by the Rho-kinase inhibitor Y-27632, which also partially inhibited the response to the TP receptor agonist U-46619, suggesting that the contractile response is due in part to Ca 2ϩ sensitization of ASM cell myofilaments.5-oxo-eicosatetraenoic acid; isometric tension; membrane potential; calcium entry; transient receptor potential; Rho-kinase INFLAMMATORY MEDIATORS, including both lipids and peptides, induce an elaborate variety of physiological and pharmacological responses that are mediated by specific receptors coupled to various effectors (11,21,23,30). A number of inflammatory lipids are derived from arachidonic acid (AA), a cell membrane component that is found esterified in the sn-2 position on the glycerol backbone of phospholipids.…”
mentioning
confidence: 99%
“…INFLAMMATORY MEDIATORS, including both lipids and peptides, induce an elaborate variety of physiological and pharmacological responses that are mediated by specific receptors coupled to various effectors (11,21,23,30). A number of inflammatory lipids are derived from arachidonic acid (AA), a cell membrane component that is found esterified in the sn-2 position on the glycerol backbone of phospholipids.…”
mentioning
confidence: 99%